ChemInform Abstract: Cyanoacetic Acid as a Masked Electrophile: Transition‐Metal‐Free Cyanomethylation of Amines and Carboxylic Acids. Issue 17 (April 2016) - Wang, Hongxiang; Shao, Ying; Zheng, Hao; Wang, Hanghang; Cheng, Jiang; Wan, Xiaobing
Abstract: A novel cyanomethylation reaction of primary aromatic amines, secondary, and even tertiary amines as well as of carboxylic acids is described.